Anaerobic capacity as a determinant of performance in sprint skiing - Losnegard, T.; Myklebust, H.; Hallen, J. (Medicine & Science in Sports & Exercise, 2012)
Purpose: As cross-country sprint competitions rely on maximal-effort durations of ~3 min, a significant anaerobic energy contribution is expected. Anaerobic energy production during supramaximal exercise has been estimated in different sports from the accumulated oxygen deficit (SO2 deficit) but, to date, not in cross-country skiing. Therefore, this study investigated the relative contribution of the aerobic and anaerobic energy systems to performance in ski skating sprint time trials using V1 and V2 techniques.